Anticonvulsant effect of the derived 4-benzoylpyridine (giz-298) on paroxysmal activity in the brain structures of rats with cobalt-induced focal epilepsy in the first stage of the formation of epileptic system - T. A. Voronina; O. I. Gaidukov; S. A. Litvinova; L. N. Nerobkova; L. A. Gmurenko (Фармакокинетика и Фармакодинамика)
He aim of the study was to investigate the influence of a derivative of 4-benzoyl pyridine connection, GIZ-298 on electroencephalographic manifestations ranvulsive activity in the brain structures of rats with cobalt-induced focal epilepsy in the first stage of the formation of epileptic system. Methodology of the study. We used the technique of creation (by an application of cobalt to the brain of rats) chronic epileptogenic focus, generating paroxysmal activity in different brain structures: the ipsi- and contralateral cortex, hippocampus and hypothalamus. The results of the study. Established that injection ofGIZ-298 at a dose of 60 mg/kg (intraperitoneally, once) on the first stage of development of the system eliminates epileptic EEG manifestations of seizure activity in all the investigated structures of the brain, with the greatest efficiency in the ipsilateral cortex and the hypothalamus, significantly reducing both the number and duration of seizure discharges.